Interaction of Parametric and Forced Vibrations in High Speed Rotor-Bearing-Systems - Bernhardt Weyh (International Journal of Rotating Machinery)
In this paper the interaction of periodic parameter excitation with forced excitations of in general non commensurable basic frequencies is under consideration. The method of enlarged systems serves as a toolbox, where the central idea of the method and the structure of the enlarged system are in the same way derived as the complete homogeneous and the manifold of inhomogeneous solutions are discussed. The application to a realisation of a high speed twin-disc rotor-bearing-system of a textile spinning turbine illustrates the resonance effects that haven’t been characterized before.